2020
DOI: 10.1039/c9ra09043f
|View full text |Cite
|
Sign up to set email alerts
|

Real-time andin situobservation of structural evolution of giant block copolymer thin film under solvent vapor annealing by atomic force microscopy

Abstract: An instrumentation technique for real-time, in situ and real space observation of microphase separation was proposed for ultra-high molecular weight block copolymer thin films (1010 kg mol À1 , domain spacing of 180 nm) under high solvent vapor swelling conditions. This is made possible by a combination of a homebuilt chamber which is capable of supplying sufficient amount of vapor, and force-distance curve measurements which gives real-time swollen film thickness and allow active feedback for controlling the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Takano et al recently demonstrated in situ AFM imaging within a sealed SVA chamber, enabling direct measurements of solvent‐swollen films. The system monitored the coarsening of fingerprint patterns in ultrahigh molecular weight PS‐b‐PMMA thin films over an 8 h period of in situ SVA imaging, shown in Figure 5 103 . DIA offers a method to overcome many of the challenges associated with SVA, fully immersing BCP films in a tunable solvent mixture, in order to maintain a finite interaction parameter for microphase separation 104,105 …”
Section: Polymer Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Takano et al recently demonstrated in situ AFM imaging within a sealed SVA chamber, enabling direct measurements of solvent‐swollen films. The system monitored the coarsening of fingerprint patterns in ultrahigh molecular weight PS‐b‐PMMA thin films over an 8 h period of in situ SVA imaging, shown in Figure 5 103 . DIA offers a method to overcome many of the challenges associated with SVA, fully immersing BCP films in a tunable solvent mixture, in order to maintain a finite interaction parameter for microphase separation 104,105 …”
Section: Polymer Applicationsmentioning
confidence: 99%
“…The system monitored the coarsening of fingerprint patterns in ultrahigh molecular weight PS-b-PMMA thin films over an 8 h period of in situ SVA imaging, shown in Figure 5. 103 DIA offers a method to overcome many of the challenges associated with SVA, fully immersing BCP films in a tunable solvent mixture, in order to maintain a finite interaction parameter for microphase separation. 104,105 AFM imaging has been extensively used to study the dynamics and mechanisms of BCP defect healing and grain coarsening during thermal annealing.…”
Section: Block Copolymer Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the thermodynamic immiscibility between the segments, several long-range order structures can be formed within a sub-micrometer scale (known as microphase separation). [1][2][3][4][5] With extensive research, the morphology of different phases is greatly affected by the Flory interaction parameters between the two segments, composition, and the overall degree of polymerization. [6][7][8][9][10][11][12][13][14] Furthermore, the material properties such as modulus, [15][16][17] conductivity, 18,19 and rheological properties 20,21 can be enhanced at the order states.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, in 2020, Hayashi and co-workers reported the real time self-assembly observation of an UHMW PS-b-PMMA (Mw = 1010 kg mol -1 ). 28 While ≈ 180 nm period lamellar features were achieved, very long solvent vapor annealing times (6 to 8 hrs) were required, which is problematic from a fabrication standpoint. Others have also demonstrated large period cylindrical patterns; 29,30 however, robust routes that use compatible solvents and truly rapid deposition methods do not exist for assembling UHMW BCPs.…”
Section: Introductionmentioning
confidence: 99%